INTERACTION DESIGN AND GAMIFICATION OF BIBIT APP TO IMPROVE FINANCIAL SELF-EFFICACY - Damayanti, Indira
A strong sense of financial self-efficacy (FSE) is not fully reflected in Indonesian society. FSE is an essential variable to enhance an individual's ability to plan and manage their finances. Low FSE can negatively impact financial decisions, including financial planning and prospects. This thesis aims to generate the interaction design of the Bibit application gamified to support the improvement of FSE in the context of saving and investing. The Bibit application was chosen due to its popularity as the most widely used investment app in Indonesia, thus offering a highly relevant solution. The gamified interaction design of the Bibit application was constructed using the Player-Centered Design (PCD) method, involving stages such as understanding the players, understanding the mission, understanding human motivation, applying game mechanics, and managing, monitoring, and measuring. Data were collected through questionnaires and interviews to evaluate the Bibit application. From the analysis conducted, the designed features that meet user needs include Quest, Retirement Fund Calculator, Emergency Fund Calculator, and Streak. These features incorporate various gamification elements, such as quests, rewards or prizes, unlockable content, levels or progression, points, personalization, and loss aversion. The effectiveness of the interaction design in supporting FSE improvement and the achievement of gamification were quantitatively measured using metrics such as the Financial Self-Efficacy Scale (FSES) for FSE and gamification missions, Intrinsic Motivation Inventory (IMI) for user motivation, Net Promoter Score (NPS) for gamification effectiveness, and the System Usability Scale (SUS) for overall usability. The percentage of respondents who experienced an increase in FSES was at least 33.33% for each FSES component, with an IMI score of 6.26, an NPS score of 66%, and an SUS score of 84.17. Based on these measurements, it can be concluded that the gamified interaction design of the Bibit application effectively supports the improvement of FSE.